Tell me [large type] - Jackson, Lisa (Center Point Large Print, 2013)
"Twenty years ago, Blondell O'Henry was convicted of murdering her eldest daughter and wounding her two other children. The prosecution said that beautiful, selfish Blondell wanted to be rid of them to be with her lover. Now Blondell's son, Niall, has recanted his testimony and demolished the case. Reporter Nikki Gillette is determined to get the true story, and not just for professional reasons. Blondell's murdered daughter, Amity, was Nikki's childhood friend. The night she died, Amity begged Nikki to meet with her, insisting she had a secret to tell, but Nikki didn't go. Her guilt is compounded by other complications--Nikki's favourite uncle, Alexander, was the attorney who helped save Blondell from execution. And rumours swirl that he was one of her many lovers. Everyone involved seems to have secrets, from Blondell's old boyfriend and his fundamentalist, snake-handling in-laws to the cop who led the original investigation."--from publisher's description.